Macroeconomic crises and poverty monitoring: a case study for India - Datt, Gaurav; Ravallion, Martin (Wiley, 1997)
Survey‐based welfare indicators can fluctuate over time in ways which have little to do with macroeconomic changes in the economy. So basing policy decisions on short‐term movements in such welfare indicators can be hazardous. There was a sharp increase in India’s poverty measures in the aftermath of the mid‐1991 crisis and the ensuing stabilization program. However, only one‐tenth of the increase in measured poverty is explicable in terms of the variables one would expect to transmit the shock to poor people. Poverty measures soon returned to their pre‐reform levels, belying the notion of a structural break induced by reforms.